APLIKASI PENCATATAN DAN ANALISIS PEMASUKAN SERTA PENGELUARAN TOKO ENSHA BERBASIS WEB DENGAN MENGGUNAKAN METODE K-MEANS - Charrisa Berliana Nathaniela; Fatah Yasin Al Irsyadi (LPPM Universitas Abdurrab, 2026)
Financial management that is still carried out manually often creates difficulties in recording and analyzing financial data. This issue is also experienced by Toko Ensha, which requires a more practical and informative financial recording system. This study focuses on designing and developing a financial recording and data analysis application by implementing the K-Means Clustering method. The system was developed using the Waterfall model, which consists of several sequential stages, including requirements analysis, system design, implementation, testing, and maintenance. The data used in this study consist of income and expenditure transactions that are compiled into monthly reports and then analyzed using the K-Means algorithm to identify financial patterns based on income, expenses, and balance. The analysis results are presented in graphical form to facilitate interpretation by the store owner. The developed application is capable of recording transactions in a structured manner, generating monthly financial reports, and providing financial analysis. Based on the testing results, the system demonstrated good performance, with all features functioning properly during Black Box Testing. Furthermore, the usability evaluation conducted using the System Usability Scale (SUS) produced an average score of 72, indicating that the system falls within the acceptable category and is considered easy to use and well accepted by users.